Effect of carbonization degree of carbon dots on cytotoxicity and photo-induced toxicity to cells. Issue 12 (December 2019) - Esfandiari, Neda; Bagheri, Zeinab; Ehtesabi, Hamide; Fatahi, Zahra; Tavana, Hossein; Latifi, Hamid
Abstract: Background: Pristine carbon dots (CDs) derived from citric acid pyrolysis are used in a variety of biomedical research such as imaging and drug delivery. However, potential cytotoxic effects of pyrolysis temperature on cells is underexplored. To address this need, we studied toxicity of the CDs to breast cancer cells using MTT and LDH assays. In addition, we investigated photo-induced cytotoxicity of the synthesized CDs in a wide concentration range under white light. Results: Our results suggest little cytotoxicity of the CDs after 24 h exposure of cells. Only the high quantum yield CDs caused a significant toxicity to cells at the highest concentrations of 2.0 and 1.5 mg/ml compared to other CDs at similar concentrations. The synthesized CDs entered the cells without any significant cytotoxicity. The CDs also caused a concentration- and irradiation time-dependent photo-induced cytotoxicity. Conclusion: The optimization of synthesis conditions from this study may help develop safe and efficient CDs for imaging and drug delivery. Abstract : Cell culture; Cell death; Cytotoxicity; Cancer research; Toxicology; Carbonization degree; Carbon dots; Cytotoxicity; Breast cancer cells; Photo-induced toxicity